Equivariant Cohomology and Deformation for Associative Algebras with a Derivation (Communications in Mathematical Research, 2025)
We introduce finite group action for associative algebras equippedwith a derivation (that is, AssDer pairs) and equivariant cohomology for suchalgebraic object. Next, we discuss equivariant deformation theory and studyits relation with the equivariant cohomology.